Halal Economy and Global Market Expansion: Opportunities and Regulatory Challenges - Pat Utomi Kareem (PT. Islamic Research Publisher, 2025)
This study examines the dynamics of the halal economy in the context of global market expansion, focusing on opportunities and regulatory challenges that shape its international development. It aims to analyze how halal economic practices interact with diverse regulatory systems across countries and how these interactions influence market access and competitiveness. The study employs a qualitative doctrinal and conceptual approach based on analysis of regulatory frameworks, policy documents, and relevant scholarly literature. Findings indicate that the halal economy demonstrates strong growth potential driven by rising demand for ethical consumption and expanding global trade networks. However, persistent regulatory fragmentation, inconsistent certification standards, and limited mutual recognition among authorities hinder full market integration. This study contributes by proposing an integrative governance framework for strengthening international coordination, harmonizing standards, and enhancing digital halal certification systems. It also highlights the strategic role of the halal economy as a driver of inclusive and sustainable global economic development in contemporary markets while emphasizing policy alignment between governments, industry actors, and certification bodies to improve transparency, trust, and efficiency in cross-border trade and supply chains worldwide. Overall, the halal economy is positioned as a strategic sector in the evolving global economic architecture, offering significant opportunities for sustainable development, ethical trade expansion, and inclusive growth, particularly for emerging markets and small and medium enterprises seeking access to international value chains, while simultaneously requiring stronger institutional cooperation, regulatory convergence, and technological innovation in certification systems to reduce barriers, enhance compliance efficiency, and strengthen consumer confidence across diverse jurisdictions in an increasingly interconnected and competitive global marketplace over the world.